2008
DOI: 10.1021/jp804766v
|View full text |Cite
|
Sign up to set email alerts
|

Probing Surface Properties of Cytochrome c at Au Bionanoconjugates

Abstract: Bionanoconjugates were created with cytochrome c from horse heart (HCc) or yeast (YCc) and citrate-stabilized gold nanoparticles (AuNPs). Evidence for the formation of stable HCc-AuNP and YCc-AuNP bionanoconjugates came from a 5 nm red-shift of the surface plasmon resonance band of the AuNPs, increase of the -potential, and direct visualization by atomic force microscopy. Langmuir isotherm fittings of -potential data indicated that higher enthalpy changes are involved in the formation of the HCc-AuNP than in Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 48 publications
7
28
0
1
Order By: Relevance
“…Since surface potential is associated to the surface charge and the thickness of the double layer, the adsorption of protein will alter these parameters. As reported previously (Brewer et al 2005;Gomes et al 2008), it is expected that an increasing amount of protein bound to the nanoparticle surface will lead to a shift in the surface potential until a stable value is observed, indicating the nanoparticle surface is saturated with protein.…”
Section: Zeta Potentialsupporting
confidence: 51%
See 2 more Smart Citations
“…Since surface potential is associated to the surface charge and the thickness of the double layer, the adsorption of protein will alter these parameters. As reported previously (Brewer et al 2005;Gomes et al 2008), it is expected that an increasing amount of protein bound to the nanoparticle surface will lead to a shift in the surface potential until a stable value is observed, indicating the nanoparticle surface is saturated with protein.…”
Section: Zeta Potentialsupporting
confidence: 51%
“…2). The AuNPs:CALNN alone presented a f-potential of -47.7 ± 0.3 mV, a value marginally higher than that obtained for citrate-stabilised AuNPs (Brewer et al 2005;Gomes et al 2008). The f-potential of the free enzyme in the same conditions (pH 7.0 and 25°C) was -17.5 ± 0.5 mV.…”
Section: Zeta Potentialmentioning
confidence: 70%
See 1 more Smart Citation
“…It could be related to differences in stability and/or interaction with serum proteins between bare and peptide-coated AuNPs. In fact, we have previously reported that the affinity of proteins to Cit-AuNPs and to AuNPs with thiol-ligands (peptides with a terminal Cys or other organic molecules) is different, despite the fact that the functional groups at the outer-surface of the AuNPs were in both cases carboxylates [40]. Although changes in the peptide sequence could affect the stability and modify NPs interactions with biomolecules [41], no major differences were observed among the three pentapeptidefunctionalized AuNPs employed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This red-shift between bare AgNPs and Cyt c-AgNP probes is related to alterations in the refractive index of AgNPs by the Cyt c layer. 21 The peak FWHM for the conjugates at pH 9.5 was relatively broadened to 123 nm, indicating that aggregates were formed by Cyt c absorbed on the Ag surface during the conjugation process. As the pH of the solution was decreased, the absorbance peak at 401 nm disappeared and a broad peak appeared newly in the range between 500 nm and 750 nm.…”
Section: Resultsmentioning
confidence: 97%